Comparison of stent retriever and intra‐arterial fibrinolysis in patients with acute ischaemic stroke. (24th February 2014) - Song, D.; Kim, B. M.; Kim, D. J.; Kim, Y. D.; Kim, J.; Lee, H. S.; Nam, H. S.; Heo, J. H.
<x xml:space="preserve">Abstract</x> Background and purpose Although the stent retriever (SR) has shown a better reperfusion rate and clinical outcome than the older generation mechanical clot retrieval device, it is uncertain whether the SR is superior to intra‐arterial fibrinolysis (IAF). Methods Ischaemic stroke patients who were treated with SR or IAF as initial endovascular treatment modality for unilateral arterial occlusion in the anterior circulation were included. Successful reperfusion was defined as Thrombolysis in Cerebral Infarction grade ≥2b. A favourable clinical outcome was defined as a modified Rankin Score ≤2 at 3 months. Results Between January 2009 and May 2012, 55 patients were treated with SR and 50 patients were treated with IAF. The baseline characteristics were similar between the two groups except for the occlusion site and rescue treatment. In binary logistic regression analysis adjusted for the occlusion site and rescue treatment, SR was independently associated with increased successful reperfusion [82.0% vs. 47.3%; odds ratio (OR) 5.21; 95% confidence interval (CI) 1.92–14.14) and a more favourable clinical outcome at 3 months (54.0% vs. 43.6%; OR 3.40; 95% CI 1.31–8.84). The frequency of symptomatic intracranial haemorrhage and mortality at 3 months was not different between the two groups. Conclusions Stent retriever was as safe as and more effective than IAF. Our findings suggest that SR may be considered as an initial modality rather than IAF in acute stroke patients who undergo endovascular treatment.